2021
DOI: 10.18844/cjes.v16i2.5648
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on women in internationalization

Abstract: Today, internationalization is among the most important strategic goals of higher education. In this context, academicians hold a significant place in academic knowledge exchange since they constitute the key mechanism in internalization. Despite this fact, female academicians continue to be underrepresented in the internationalization of higher education. Considering the emphasis on Sustainable Development Goal 5, which states that gender equality is the basis of sustainable development for all individuals un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Since national languages are often generally used in fields where we have national applications, data from other citation indices with more regional content, such as the Arabic Citation Index, might also be used in future work to provide more comprehensive analysis for policy makers Several possible reasons have been described to explain the evidence that men publish more than women during their career Larivière et al, 2011;Xie et al, 2003) such as differences in family responsibilities (Carr et al, 1998;Fox, 2005;Stack, 2004), academic rank (Van den Besselaar & Sandström, 2017), or career absence (Cameron et al, 2016). Some have argued that women's attrition in science is primarily attributed to women's personal motives and the notion of societal division of labour (Ceci & Williams, 2011;Ceci et al, 2009;Fox, 2005Fox, , 2006Fox et al, 2017;Tasci, 2021). Why are there more men than women starting a career as a publishing researcher?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since national languages are often generally used in fields where we have national applications, data from other citation indices with more regional content, such as the Arabic Citation Index, might also be used in future work to provide more comprehensive analysis for policy makers Several possible reasons have been described to explain the evidence that men publish more than women during their career Larivière et al, 2011;Xie et al, 2003) such as differences in family responsibilities (Carr et al, 1998;Fox, 2005;Stack, 2004), academic rank (Van den Besselaar & Sandström, 2017), or career absence (Cameron et al, 2016). Some have argued that women's attrition in science is primarily attributed to women's personal motives and the notion of societal division of labour (Ceci & Williams, 2011;Ceci et al, 2009;Fox, 2005Fox, , 2006Fox et al, 2017;Tasci, 2021). Why are there more men than women starting a career as a publishing researcher?…”
Section: Discussionmentioning
confidence: 99%
“…To achieve true gender parity in MENA, several impediments on the societal, structural, institutional, and legal levels must be overcome simultaneously (Momani, 2016). Tasci (2021) has also provided a few recommendations to strengthen women scientists in the international research landscape. In the end, determining the best policies is very reliant on the context of each country.…”
Section: Discussionmentioning
confidence: 99%
“…These differences do not imply that women will be less effective in business than their men counterpart, but only that they may adopt different approaches which may not be equally as effective as the approaches adopted by men [23]. Socialist feminist theory also drew attention to the fact that the differences in the division of labor existed among women of different classes [24].…”
Section: Social Feminism Theorymentioning
confidence: 99%
“…Women academics are one of the groups apparently influenced by the conditions that the pandemic caused (Deryugina et al, 2021;Minello, 2020;Oleschuk, 2020;Parlak et al, 2021;Pinho-Gomes et al, 2020;Tasci, 2021;Yildirim & Eslen-Ziya, 2020). With the COVID-19 pandemic, the sudden change in the system caused the transition to distance education and learning, more time was spent on house chores and on child and elderly care, the psychological health needs of students and faculty increased, and the time available for academic studies decreased (Deryugina et al, 2021;Minello, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With the loss of childcare and the changing working conditions, new demands arose, and the domestic workload of women increased (Minello et al, 2020;Petts et al, 2020;Parlak et al, 2021;Wenham et al, 2020). As a result of gender inequalities in-home responsibilities, women's academic productivity and scientific output were affected more negatively (Deryugina et al, 2021;Gabster et al, 2020;Tasci, 2021;Vincent-Lamarre et al, 2020). Studies showed that women submitted proportionally fewer manuscripts than men during the COVID-19 lockdown months (Squazzoni et al, 2020;Vincent-Lamarre et al, 2020).…”
Section: Introductionmentioning
confidence: 99%